Peranan Media Sosial dan Teknologi Informasi Dalam Memajukan Pembangunan Daerah - Havid Syafwan; Pristiyanilicia Putri; Masitah Handayani (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The use of social media today is very large and has an impact on the social life of the wider community in line with the development of Information Technology. The existence of social media can certainly reduce human limitations in interacting and communicating with each other. One of the positive things about the use of social media is in conveying information quickly to the wider community, especially in advancing development in the region. The devotional activities are carried out in the form of socialization or delivering short materials followed by discussions where this activity aims to provide insights on the use of social media that is good and correct to provide benefits for its users. Participants in this activity are members of the community who are members of the Asahan Development Role Institute (LEPPAS). The result of this devotion activity is in the form of material understanding for the participants of activities that will be able to implement the role of social media in advancing regional development, especially in Asahan Regency.